Immuno - Functionalized Silver Nanoparticles for Diagnostics, Therapeutics and Protection of Rabies Viral Infection - Anitha Sironmani, Thangamuthu (Current Nanomedicine, 2017)
Introduction: Rabies, the most fatal of all infectious diseases, remains a major public health problem in developing countries. The presence of neutralizing and nonneutralizing antiviral antibodies in the serum and cerebrospinal fluid suggests that immune responses are not only responsible for virus clearance but also contribute to pathogenesis revealing the possibility of autoimmunity causing the death. In spite of the developments of costly vaccines, there is no cure for this infection as the drugs etc. do not cross the blood brain barrier to treat the encephalitis in the brain and cerebrospinal and other neural systems. The neuroinvasive functionalized silver nanoparticles with whole viral antigen/ antibodies can neutralize the autoantibody/antigens restoring the neurological dysfunction arise due to autoimmunity. Methods: Commercially available veterinary rabies vaccines were used for functionalization of nanoparticles for all animal studies and for human use commercial human vaccines were used. The immuno-dominant polypeptides for neutralization and bio distribution studies were carried out. The field trial was carried out to rapid dogs, cattle and one human. Results: The present invention - The nanoformulation elicits an optimal immuno protective response against rabies antibody /virus by neutralizing auto immune antibodies/ virus / antigens of rabies infection. The distribution pattern in various tissues and neutralization with these functionalized nanopreparation strongly recommend the use for prophylactic, therapeutic and diagnostics. This novel innovative strategy cures rabies infection which causes 100% mortality within 2 hr to 12 hrs as proved by the field trial report. Discussion: The low cost nanofomulations, in single minimum dosage, with high stability and without cold chain storage could neutralize all the autoantibody/antigens restoring the neurological dysfunction. This novel innovative strategy signifies the birth of a new era in therapeutics for all microbial infections leading to autoimmune diseases.
Keywords: nanotechnology for nematode infection